ANALISIS HASIL BELAJAR MATEMATIKA MATERI BILANGAN BULAT SISWA KELAS 3 SD NEGERI 02 KARANG MELATI (JS (JURNAL SEKOLAH), 2021)
Abstract:. The purpose of research on the analysis of learning outcomes carried out by researchers is to determine student learning outcomes in mathematics subjects, adding and subtracting whole number arithmetic operations for third grade students of SD Negeri 02 Karang Melati in the 2021/2022 academic year.This research method uses a quantitative approach. The research method used is descriptive quantitative method. This research methodis a way of collecting data by means of observation, documentation and tests.Student learning out comes that have been analyzed are students who have student learning outcomes with very high criteria as many as 9 people with a value of 100 from theten questions given by the teacher, students who have the ability to learn student outcomes with high criteria are 7 people with a score of 80 with a total of 10 questions that have been given by the teacher, students who have student learning outcomes with moderate criteria, namely 7 people with a score of 70 KKM standards that have been determined by the teacher, andstudents who have learning outcomes with low criteria, namely only 1 person with a score of 60 out of 10 questions which has beengiven.Keywords: Analysis, Student Learning Outcomes, Mathematics SubjectsAbstrak:Tujuan penelitian pada analisis hasil belajar yang dilakukan oleh peneliti adalah untuk mengetahui hasil belajar siswa pada mata pelajaran matematika materi operasi hitung penjumlahan dan pengurangan bilangan bulat siswa kelas 3 SD Negeri 02 Karang Melati tahun ajaran 2021/2022. Metode penelitian ini menggunakan pendekatan kuantitatif. Adapun metode penelitian yang digunakan adalah metode deskriptif kuantitatif. Metode penelitian ini cara pengumpulan data dengan cara observasi, dokumentasi dan tes. Hasil belajar siswa yang telah dianalisis siswa yang memiliki hasil belajar siswa dengan kriteria sangat tinggi sebanyak 9 orang dengan nilai 100 dari kesepuluh soal yang diberikan oleh guru, Siswa yang memiliki kemampuan hasil belajar siswa dengan kriteria tinggi yaitu sebanyak 7 orang dengan nilai 80 dengan jumlah 10 soal yang telah diberikan oleh guru, siswa yang memiliki hasil belajar siswa dengan kriteria sedang yaitu sebanyak 7 orang dengan nilai 70 setandar KKM yang telah ditentukan oleh guru, dan siswa yang memiliki hasil belajar dengan kriteria rendah yaitu hanya 1 orang dengan nilai 60 dari 10 soal yang telah diberikan.Kata Kunci: Analisis, Hasil Belajar Siswa, Mata Pelajaran Matematika